The Effect of Counselling and Administration of Sweet Potato Leaf Decoction on Uterine Involution and Smooth Breastfeeding in Postpartum Mothers 1-7 Days - Sofia Mawaddah; Annisa Nor Yulia (EMBRIO: Jurnal Kebidanan, 2023)
The survey results at the UPT Pahandut Health Center, Palangka Raya City, the coverage of babies who do not receive exclusive breastfeeding in 2021 is 163 babies. Alternative measures or management are needed in the form of consuming foods or ingredients that are believed to increase milk supply. The purpose of this study was to determine the effect of counselling and administration of sweet potato leaf decoction on uterine involution and smooth breastfeeding in postpartum mothers for 1-7 days in the working area of ​​the Pahandut Health Center. The type of research used was a quasi-experiment with a two-group pretest-posttest research design before being given treatment and after being given treatment. The total sample is 54 people. The results of the study showed that there was an effect of counselling and sweet potato leaf decoction on uterine involution and smooth breastfeeding p values ​​0.010 and 0.020 (less than 0.05). H0 is rejected and H1 is accepted. There is an effect of giving counselling and decoction of sweet potato leaves on uterine involution and the smoothness of breastfeeding in postpartum mothers 1-7 days in the working area of ​​the Pahandut Health Center.